Significant of Antibiotic prophylaxis for diabetic patients with periodontal disease, 1 hour before phase 1 periodontal therapy - Shrestha, Puja; Iqbal, Md Ashif; Bristy, Orin Chowdhury; Shrestha, Nimesh (Update Dental College Journal, 2020)
People with diabetes are more likely to have periodontal diseases than people without diabetes. Periodontal disease is often considered a complication of diabetes. On the other hand, severe periodontal disease can increase blood glucose levels. Special care and management protocol need to be addressed to patients with diabetes during periodontal therapy. Systemic antibiotics in conjunction with scaling and root planning can offer an additional benefit over SRP alone in the treatment of periodontitis. This review aims to evaluate the significance of antibiotic prophylaxis for diabetic patients with the periodontal disease before 1 hour/ 1-2 days of phase 1 periodontal therapy. The goal of antibiotic prophylaxis is to prevent the onset of injections through the entranceway provided by the therapeutic action. But currently, no established guidelines are in place for antibiotic prophylaxis before periodontal therapy. Update Dent. Coll. j: 2020; 10 (1): 28-30